The Mediterranean Diet and Cancers in Italy: Stochastic and Non-Stochastic Analysis - Cornelli, Umberto; Grossi, Enzo; Recchia, Martino; Cestaro, Benvenuto; Rondanelli, Mariangela; Cazzola, Roberta; Pistolesi, Elvira (European Journal of Applied Sciences, 2023)
Background: The relationship between foods and cancers has been documented in many epidemiological and cohort studies of the Mediterranean Diet (MeD). Objective: Correlation between food expenditure in Italy and the prevalence of nine cancers: breast, prostate, colon, pancreas, TBL (throat-bronchial-lung), bladder in males and females, uterus, and ovaries, with a comparison of differences between Northern and Southern Italy. Methods: The expenditure of 19500 Italian families on the 56 most sold food categories was taken from ISTAT (Italian National Institute of Statistics) records for 2016. These data were then correlated with the prevalence of death from the nine above mentioned cancers in 2020. Stochastic and non-stochastic analyses were used to determine the correlations between foods and cancers. Results: None of the cancers showed identical protective or causative food patterns. The data confirmed the causative role of wine and the protective role of pasta, flour and sugar. Surprisingly fish and olive oil were found to be causative for some cancers. Southern Italy showed significantly lower prevalence of cancer due to a lower consumption of causative foods and higher consumption of protective ones. Conclusion: MeD has changed in Italy. Some causative and protective foods were found for all the cancers, but none had the same pattern. However, foods can be considered important co-factors in cancer development. Pasta, flour and sugar were shown to be protective for many cancers and, besides wine, some other foods, like olive oil and fish, were causative for some cancers. The correlation between food expenditure and disease seems to be a valid, simple research method.